Investigating the Effects of Technology on Nastaliq Script - Kaspour, Hoda; Chareie, Abdolreza; Asadi, Morteza; Haseli, Parviz (Journal of History Culture and Art Research, 2018)
Calligraphy, since its formation, has witnessed an innovative transformation. Developments in the printing industry have significantly influenced its evolution. In script work, speed and accuracy have always been important elements; however, the existence of technological tools has led to a significant number of calligraphic tasks without calligraphist. The main purpose of this research is to explain the changes brought by the use of technological tools in calligraphy. The contradiction or coordination of traditional aspects of calligraphy with different dimensions of technology and the concern for the collapse of calligraphy by this phenomenon necessitates this research. In today’s world, writings are created by technological tools with special software features in cyberspace, and the letters and words are combined with the same principles and rules of traditional writing in the computer environment. The factors that led calligraphy to change in technology are the main issues in this research.